Fusobacterium nucleatum: The Opportunistic Pathogen of Periodontal and Peri-Implant Diseases - Chen, Yanchi; Shi, Tao; Li, Yiling; Huang, Linyang; Yin, Derong (Frontiers in Microbiology, 2022)
Peri-implant diseases are considered to be a chronic destructive inflammatory destruction/damage occurring in soft and hard peri-implant tissues during the patient’s perennial use after implant restoration and have attracted much attention because of their high incidence. Although most studies seem to suggest that the pathogenesis of peri-implant diseases is similar to that of periodontal diseases and that both begin with microbial infection, the specific mechanism of peri-implant diseases remains unclear. As an oral opportunistic pathogen, Fusobacterium nucleatum (F. nucleatum) has been demonstrated to be vital for the occurrence and development of many oral infectious diseases, especially periodontal diseases. More notably, the latest relevant studies suggest that F. nucleatum may contribute to the occurrence and development of peri-implant diseases. Considering the close connection between peri-implant diseases and periodontal diseases, a summary of the role of Fusobacterium nucleatum in periodontal diseases may provide more research directions and ideas for the peri-implantation mechanism. In this review, we summarize the effects of F. nucleatum on periodontal diseases by biofilm formation, host infection, and host response, and then we establish the relationship between periodontal and peri-implant diseases. Based on the above aspects, we discuss the importance and potential value of F. nucleatum in peri-implant diseases.